4, 4′-Diisothiocyanatostilbene-2, 2′-disulfonate modulates voltage-gated K+ current and influences cell cycle arrest in androgen sensitive and insensitive human prostate cancer cell lines. (12th June 2020) - George, Kiran; Thomas, Nisha Susan; Malathi, Raman
Abstract: The stilbene derivative, 4, 4′-diisothiocyanatostilbene-2, 2′-disulphonic acid (DIDS), an anion channel blocker is used in the present study to evaluate its modulatory effect on voltage-gated K + current (IK ) in human prostate cancer cell lines (LNCaP and PC-3). Voltage-gated K + (KV ) channels in the plasma membrane are critically involved in the proliferation of tumor cells. Therefore, KV channels are considered as a novel potential target for cancer treatment. The results of the present study show that the external perfusion of DIDS activates IK in a concentration-dependent manner, although the known K + channel blocker TEA failed to block the DIDS activated IK in PC-3 cells. Whereas, in LNCaP cells, the higher concentration of DIDS blocked IK, though this effect was not completely recovered after washout. The difference in function of DIDS might be due to the expression of different Kv channel isoforms in LNCaP and PC-3 cells. Further, the anticancer studies show that treatment of DIDS significantly induced G2/M phase cell cycle arrest and induced moderate and low level of cell death in LNCaP and PC-3 cells respectively. This finding reveals that DIDS modulates IK and exerts cell cycle arrest and cell death in LNCaP and PC-3 cells.